Method for Optimizing the Kinematic Scheme of Stretch-Forming Parts from Sheet Blanks - Bormotin Konstantin (EDP Sciences, 2021)
The modeling of the stretch-forming process a sheet on a punch is considered. A numerical method has been developed for solving the optimal control problems of the stretch-forming process sheet blanks. The values of the residual displacements are considered as an optimization criterion. The algorithms implemented in CAE allow calculating the optimal parameters for the operation of the CNC stretch-forming press. The simulation results are compared with full-scale experiments on the shaping of sheet parts on a stretch-forming press T-600.